Bone Connectivity and the Evolution of Ichthyosaur Fins - Fernández, Marta Susana (2024)
After the end-Triassic extinction, parvipelvian ichthyosaurs diversified and became dominant elements of marine ecosystems worldwide. By the Early Jurassic, they achieved a thunniform body plan that persisted for the last 100 m.y.a of their evolution. Diversification and extinctions of thunniform ichthyosaurs, and their swimming performance, have been studied from different perspectives. The transformation of limbs into hydrofoil-like structures for better control and stability during swimming predates thunniform locomotion. Despite their importance as control surfaces, fin evolution among thunnosaurs remains poorly understood. We explore ichthyosaur fin diversity using anatomical networks. Our results indicate that, under a common hydrofoil controller fin, the bone arrangement diversity of the ichthyosaur fin was greater than traditionally assumed. Changes in the connectivity pattern occurred stepwise throughout the Mesozoic. Coupled with other lines of evidence, such as the presence of a ball-and-socket joint at the leading edge of some derived Platypterygiinae, we hypothesize that fin network disparity also mirrored functional disparity likely associated with different capabilities of refined maneuvering. The ball-and-socket articulation indicates that this local point could be acting like a multiaxial intrafin joint changing the angle of attack and thus affecting the maneuverability, similar to the alula of flying birds. Further studies on large samples and quantitative experimental approaches would be worthy to test this hypothesis.